PENGARUH STRATEGI PEMBELAJARAN LEARNING CYCLE DAN GAYA BELAJAR TERHADAP HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM SISWA MADRASAH DINIYAH TAKMILIYAH AWALIYAH UBUDIYAH KOTA PEMATANG SIANTAR - Muhammad Rusli (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study was to find out: (1) differences in learningoutcomes of Islamic Culture History of students taught with learnig cyclelearning strategies with students taught with expository learningstrategies, (2) differences in learning outcomes of Islamic Culture Historyof students who have visual learning styles, auditory and kinesthetic, and(3) the effect of learning cycle learning strategies and student learningstyles on the results of learning Islamic Cultural History. The method ofthis research is quasi-experimental with the population of this study arefourth grade students (four) Madrasah Diniyah Takmiliyah AwaliyahUbudiyyah 2018/2019 school year consisting of 2 (two) classes. Thesample selected cluster random sampling technique in terms of the classwith the learning cycle learning strategy is class IV1 with 31 students,while students taught with expository strategies are students of class IV2with 34 students. The instruments of data collection are questionnairesand test results. Technique by analysis of variance (Anova) at = 0.05. Theresults of this study are: (1) student learning outcomes taught withlearning cycle learning strategies ( X = 33.22) higher than student learningoutcomes taught with expository learning strategies ( X = 27.94), withFcount = 89.49 > Ftable = 3.988, (2) student learning outcomes with visuallearning styles ( X = 34.26) are higher than student learning outcomes withkinesthetic learning styles ( X = 28.38) and auditory learning styles (( X =27.69), with Fcount = 62.49 > Ftable = 3.988, and (3) there is an interactionbetween learning strategies and learning styles towards learning outcomeswith statistical calculations known Fcount = 47.06 > Ftable = 3.988.